Exploring the potential of calcium-fortified sweet potato noodles for osteoporosis prevention: Insights from in vivo rat studies - Ambarwati , Karsi; Giriwono, Puspo E.; Handharyani, Ekowati; Yasni, Sedarnawati (Narra J, 2025)
Calcium (Ca) deficiency is a primary contributor to osteoporosis, a condition characterized by low bone density and increased fracture risk. Fortifying widely consumed foods with calcium is one approach for addressing this insufficiency. Given the popularity of noodles, adding Ca to them offers a promising approach to enhancing Ca intake within communities. The aim of this study was to investigate the effects of Ca-fortified sweet potato noodles on osteoporosis prevention. This study used 4-month-old Sprague-Dawley rats. A completely randomized design was used with four treatment groups: CS (SHAM, control diet), CO (Sham, test diet), US (OVX, control diet), and UO (OVX, test diet). Both control and test diets, which included Ca-fortified sweet potato noodles, were administered to OVX (ovariectomy-induced osteoporosis model) and SHAM (control for surgical procedure) groups for two months. At the end of the experiments, serum Ca levels were collected and analyzed for Ca and alkaline phosphatase (ALP) levels and their bones were analyzed for physical properties and bone mineral density (BMD) using X-ray analysis. Data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan as a post hoc test. The intervention of Ca-fortified sweet potato noodles for two months significantly increased serum Ca levels and reduced ALP levels compared to controls, both in SHAM (Ca: 38.03±0.877 mg/dL; ALP: 355±38.0 IU/L) and OVX (Ca: 36.18±2.810 mg/dL; ALP: 340±5.5 IU/L) groups. The test diet maintained the ratio of bone weight to bone volume and preserved the Ca content in the rats' bones. OVX rats consuming the test diet for two months exhibited significantly higher femur bone strength than OVX rats consuming the control diet (test: 6.50±0.300 kg; control: 4.83±0.289 kg). There was no significant difference in BMD between the SHAM and OVX groups on the test diet, indicating that the test diet can maintain bone BMD despite accelerated aging. These findings suggest that Ca-fortified sweet potato noodles can serve as a dietary Ca source, contributing to the prevention of osteoporosis by maintaining serum Ca levels, preserving bone Ca content, as well as maintaining bone density and strength.